2019
DOI: 10.24931/2413-9432-2019-8-2-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic effectiveness of laser diode combined with ozone to reduce STaphylicoccus aureus biofilm with exogenous chlorophyll of Dracaena angustifolia leaves

Abstract: Photodynamic inactivation is an effective treatment that uses light irradiation, photosensitizer and oxygen. The aim of this study was to determine photodynamic effectiveness of laser diode combined with ozone to reduce Staphylococcus aureus biofilm using exogenous chlorophyll (Chlo). The chlorophyll was extracted from leave of Dracaena angustifolia. To determine the antibacterial effect of S. aureus biofilm treatments, samples were separated into Chlo, Laser, Chlo+Laser, Ozone, Ozone+Laser, Chlo+Ozone+Laser c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
(1 reference statement)
0
6
0
1
Order By: Relevance
“…Biofilm research is also found in other journals. 22,23 The difference in the reduction rate of PDT increased when ozone was added, thus helping biofilm reduction compared to PDT. 22 The results showed that the Chlo+Ozon+Laser combination treatment at 20 seconds of ozone exposure with 4 minutes irradiation time caused a decrease in biofilm activity by 80.26%, which was the highest efficacy of all treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm research is also found in other journals. 22,23 The difference in the reduction rate of PDT increased when ozone was added, thus helping biofilm reduction compared to PDT. 22 The results showed that the Chlo+Ozon+Laser combination treatment at 20 seconds of ozone exposure with 4 minutes irradiation time caused a decrease in biofilm activity by 80.26%, which was the highest efficacy of all treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Усиление антибактериального эффекта в культуре золотистого стафилококка было отмечено группой авторов при использовании люминофора хлорофилла за счет переизлучения в красную область видимого спектра [14].…”
Section: оригинальные статьи Original Articlesunclassified
“…Chlorophyll is a green substance found in green plants that photosynthesizes. 13 In photosynthesis, chlorophyll acts as a light catcher, energy transfer, and light conversion and can absorb a maximum wavelength between 400-700 nm. 14 Curcumin is a curcuminoid compound with yellow pigment in turmeric rhizome, which is antitumor, antioxidant, anticarcinogenic, anti-inflammatory, antiviral, antifungal, antispasmodic, and hepatoprotective.…”
Section: Introductionmentioning
confidence: 99%